An inhibitor-free, versatile, fast, and cheap precipitation-based DNA purification method - Zhe F. Tang; David R. McMillen (PLoS ONE, 2025)
Nucleic acid purification is a key step in molecular biology workflows, and especially critical in synthetic biology. Two common techniques are phenol chloroform extraction and silica column adsorption. We have determined that commercial silica columns appear to elute a currently unidentified substance that can inhibit subsequent enzymatic reactions if not sufficiently diluted. To resolve this inhibition, we have developed a novel purification approach in which we achieve simultaneous protein removal and DNA precipitation through the application of chaotropic salts and alcohol/polyethylene glycol. While prior DNA precipitation approaches require 2 steps to remove protein and precipitate DNA, and 4 steps to remove RNA and precipitate DNA, our method accomplishes all of them in a single step. Our approach matches the speed and versatility of silica column purification while additionally being substantially cheaper, as well as avoiding restrictions on the maximum size of purified DNA fragments and the need for gel extraction to remove primer dimers below 700 bps. Our purification technique has also enabled us to uncover an important insight into nucleic acids: Gibson Assembly generates mainly linear DNA that transforms poorly into the cloning host E. coli, which is linked to suboptimal levels of functional colony formation after transformation. We show that decreasing the concentration of the linear DNA by 100-fold dramatically increases circularization.